REVITALISASI PELAKSANAAN KETENTUAN PERATURAN PEMERINTAH DAN PEMEGANG IZIN PERTAMBANGAN DALAM MENYIKAPI PELESTARIAN KEANEKARAGAMAN HAYATI DI KAWASAN HUTAN - Ardhana, I Putu Gede (Bumi Lestari; Vol 11 No 1 (2011), 2011)
This Article aims to study the governmental policy for methods which participate the act No. 19 of 2004th concerning the perspective preservation of biodiversity. This Article represent the normative legal research that is concern with legislation approach (the statute approach), case study approach (the case approach), approach by factual (the fact approach), the approach of analytical legal concept (analytical conceptual approach), and the bibliography approach (the library approach) that is the collection of the reading materials related with this topic of problems. From the conclusion of this article, we can obtain the summary that act No. 19 of 2004th was the concretion of synchronized activity of the mining industry in the forest zone and threatens the preservation of biodiversity. To remove this threaten we must revitalize the methods which enact laws and regulations concerning with forestry, conservation of biodiversity, and ecosystem against the mining’s operation. Especially against the conduct of 13 mining companies which are authorized by permissions of the mining industry for exploitation, the sanction agents the offender accurately must be imposed and must be accordance with the law or regulation in force for methods which guarantee the reservation of biodiversity.
Keywords: mining, forest zone, preservation, biodiversity, law, regulation